Pengukuran Tekanan Absolut Biogas Berbahan Campuran Eceng Gondok Dan Kotoran Sapi - Riswanto Riswanto; Sodikin Sodikin (Department of Physics Education, Universitas Mataram, 2019)
Biogas techniques is a way to produce energy with the anaerobic process by utilizing organic ingredients, one of which can be derived from herbs. The quality of biogas production can be viewed by performing the measurement of absolute pressure of biogas. Absolute pressure is the atmospheric pressure coupled with the measured pressure.ÃÂ The magnitude of the pressure will affect the quality of the flame produced biogas. This study, using the method of observation, and measurements. As for the data analysis techniques,. The findings focused to find the different of biogas production by measuring the change in absolute pressure of biogas. Measurements are done using a manometer. The results obtained show that the introduction by using cow dung retrieved changes pressure biogas occurred on day 3 with pressure 140.565 N/m2, the characteristics of the data graph illustrates the R2 = 0.677. Different results are indicated on the mixing water hyacinth with cow manure, biogas pressure changes happen on day 1 with the characteristic graph of a R2 = 0.976. This condition describes that the mixing of the water hyacinth and cow dung provides distinctions signifikant in accelerating the process of occurrence of biogas.